2015
DOI: 10.1371/journal.pone.0139976
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Ureterorenoscopy Is Associated with Increased Intravesical Recurrence following Radical Nephroureterectomy in Upper Tract Urothelial Carcinoma

Abstract: Diagnostic ureterorenoscopy is powerful tool to confirm upper tract urothelial cancer (UTUC). However, URS and associated manipulation may be related to the risk of intravesical recurrence (IVR) following radical nephroureterectomy (RNU). We aimed to investigate whether preoperative ureterorenoscopy would increase IVR after RNU in patients with UTUC. We performed a retrospective analysis of 630 patients who had RNU with bladder cuff excision due to UTUC. Diagnostic URS was performed in 282 patients (44.7%). Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 29 publications
6
67
0
1
Order By: Relevance
“…Sankin et al [9] also found the same relationship between time delay and risk for IVR. In contrast, Sung et al [11] revealed that the concurrent and delayed RNU after URS did not make any difference in the incidence of IVR or time to bladder recurrence, making the issue more complicated. In addition, Nison et al [12] reported that the use of diagnostic URS did not alter the risk of CSS, RFS, or MFS as well as muscle-invasive lesions.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Sankin et al [9] also found the same relationship between time delay and risk for IVR. In contrast, Sung et al [11] revealed that the concurrent and delayed RNU after URS did not make any difference in the incidence of IVR or time to bladder recurrence, making the issue more complicated. In addition, Nison et al [12] reported that the use of diagnostic URS did not alter the risk of CSS, RFS, or MFS as well as muscle-invasive lesions.…”
Section: Discussionmentioning
confidence: 97%
“…The general descriptions of included studies were summarised in Table 1. Among the included studies, 7 (60%) were from Asian countries [8, 10, 11, 13, 14, 17] and 3 studies were conducted in USA [9, 15, 16] and one in France [12], respectively. A total of 4,057 participants were included in the subsequent meta-analysis, of which 518 patients had a history of TCC in bladder.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, several studies have demonstrated an association between postsurgical positive cytology and urothelial tumor recurrence for both TURBT and radical nephroureterectomy . Finally, 2 studies examined the inverse principle and demonstrated that ureteroscopy of the upper tract within the setting of high‐grade urothelial carcinoma is associated with intravesical recurrences, with a likely mechanism of high pressure irrigation in the upper tract dislodging high‐grade cells, resulting in lower tract implantation . These observations, taken together, suggest that although the theoretical risk may be low, within the setting of positive cytology, viable tumor cells are likely to be present in the bladder and could result in upper tract implantation, especially within the setting of urothelial trauma.…”
Section: Discussionmentioning
confidence: 93%